ROLE OF CONFLICT REPORTING IN NIGERIA - Obasi, Ferdinand; Ugwuanyi, Felix O.; Agu, Nicholas; Ogbuka, Obinna (African Journal of Social and Behavioural Sciences, 2025)
The study examined the role of conflict reporting in managing and reducing conflicts in Nigeria. It reviewed historical patterns of conflict and analysed how journalists shaped public understanding through their reporting choices. The paper explained that responsible coverage, built on fact-checking, neutrality, balanced framing, and giving voice to affected groups, helped to reduce tension and support peacebuilding. It also showed that mature and well-trained journalists are better equipped to handle the pressures, risks, and ethical demands of conflict situations. Overall, the study argued that conflict reporting was most effective when journalists adopted human-centred, non-violent approaches that promoted dialogue, protected national security, and strengthened public trust.